SOME CORRELATIONS BETWEEN DEVELOPMENT AND RESPIRATION IN THE SAND DOLLAR EGG, AS SHOWN BY CYANIDE INHIBITION STUDIES - Robbie, W. A. (The Rockefeller University Press, 1948)
Cyanide is a valuable tool for studying respiratory mechanisms and their rôle in embryonic development: it is relatively specific in its action, penetrates cell membranes readily, is active in low concentration, and may be controlled quantitatively (page 217). Echinarachnius is extremely sensitive to cyanide and the oxygen consumption of both eggs and of sperm is almost completely inhibited by 10(–5) M HCN (pages 219 and 221). Cell division is likewise arrested by the same concentration (page 223). One of the pronounced effects of an irreversible dosage of cyanide is the marked cytolysis or breakdown of the egg, both internally and at the cell membrane. This cytolysis appears to be related to the state of metabolism, and its occurrence varies with both the respiratory and developmental activity of the cell (page 224). The lethal dosage of cyanide varies with the state of development of the egg: the unfertilized egg is less susceptible than the fertilized one, and the susceptibility increases as the development of the fertilized egg proceeds (page 228). The Echinarachnius egg differs from that of Arbacia in respiratory behavior chiefly in its inability to survive prolonged anoxia: the sea urchin egg will tolerate for 24 hours a concentration of cyanide that kills the sand dollar eggs in 30 minutes (page 229). The Echinarachnius egg is apparently completely dependent upon cyanide-sensitive catalytic systems for its normal functioning and maintenance. Interference with this aerobic energy release mechanism results in irreversible damage to the egg (page 231).